1994
DOI: 10.1007/bf00201674
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion mapping of the gene for X-linked neural tube defects in an Icelandic family

Abstract: Various polymorphic markers with a random distribution along the X chromosome were used in a linkage analysis performed on a family with apparently X-linked recessive inheritance of neural tube defects (NTD). The lod score values were used to generate an exclusion map of the X chromosome; this showed that the responsible gene was probably not located in the middle part of Xp or in the distal region of Xq. A further refining of these results was achieved by haplotype analysis, which indicated that the gene for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Pedigrees for two families, which have not been published previously, are shown in Figure 1. Although linkage studies and haplotype analysis in a third family from Iceland appear to exclude the region containing the ZIC3 gene (Xq26) [Hol et al, 1994], they were included in our studies because of the ease of sequencing the gene to provide definitive exclusion of ZIC3 as a candidate.…”
Section: To the Editormentioning
confidence: 99%
“…Pedigrees for two families, which have not been published previously, are shown in Figure 1. Although linkage studies and haplotype analysis in a third family from Iceland appear to exclude the region containing the ZIC3 gene (Xq26) [Hol et al, 1994], they were included in our studies because of the ease of sequencing the gene to provide definitive exclusion of ZIC3 as a candidate.…”
Section: To the Editormentioning
confidence: 99%
“…The largest of these families originated from Iceland [Jensson et al, 1988] and has been the subject of several linkage studies. One study setting a penetrance for the disorder at 70% suggested that Xq12‐q24, which coincides with the localization of NAP1L2 , was one of two regions that cosegregates in the family [Hol et al, 1994]. However, the other study, in which exclusively 100% penetrance for expression of the phenotype was considered, failed to detect linkage—possibly due to the small number of available carriers/affected individuals and a lack of informative markers [Newton et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports describing anencephaly in families with an X‐linked pattern of inheritance [Baraitser and Burn, 1984; Toriello, 1984; Jensson et al, 1988]. Some of the families studied did not show linkage to 62 markers on the X chromosome suggesting that the susceptibility gene maps elsewhere on one of the autosomes [Hol et al, 1994; Newton et al, 1994]. The other syndromic causes are either sporadic conditions or those with unknown inheritance, and include Axelrod syndrome, Diprosopus, hemihypertrophy‐hemihypaesthesia‐hemiareflexia‐scoliosis, Medeira syndrome, meroanencephaly, schisis association, and XK‐aprosencephaly.…”
Section: Syndromes and Ntdsmentioning
confidence: 99%